Pengaruh Persepsi Kemudahan dan Persepsi Manfaat Terhadap Niat Beli Ulang Secara Online dengan Kepuasan sebagai Variabel Intervening - Khoirul Basyar; Sanaji Sanaji (Universitas Negeri Surabaya, 2018)
The purpose of this study to analyze the effect of perceived ease of use and perceived usefulness on online repurchase intention that mediating of satisfaction variable. Samples taken as many as 210 peoples. Measuring instruments used are questionnaire data analysis using path analysis.The results showed that the perceived ease of use dan perceived usefulness having a positive and significant influence towards satisfaction. Perceived ease of use dan perceived usefulness having a positive and significant effect against online repurchase intention . The satisfaction of having a positive and significant effect against online repurchase intention.